Association Study of the 5′UTR Intron of the FAD2-2 Gene With Oleic and Linoleic Acid Content in Olea europaea L. - Salimonti, Amelia; Carbone, Fabrizio; Romano, Elvira; Pellegrino, Massimiliano; Benincasa, Cinzia; Micali, Sabrina; Tondelli, Alessandro; Conforti, Francesca L.; Perri, Enzo; Ienco, Annamaria; Zelasco, Samanta (Frontiers in Plant Science, 2020)
Cultivated olive (Olea europaea L. subsp. europaea var. europaea) is the most ancient and spread tree crop in the Mediterranean basin. An important quality trait for the extra virgin olive oil is the fatty acid composition. In particular, a high content of oleic acid and low of linoleic, linolenic and palmitic acid is considered very relevant in the health properties of the olive oil. The oleate desaturase enzyme encoding-gene (FAD2-2) is the main responsible for the linoleic acid content in the olive fruit mesocarp and, therefore, in the olive oil revealing to be the most important candidate gene for the linoleic acid biosynthesis. In this study, an in silico and structural analysis of the 5’UTR intron of the FAD2-2 gene was conducted with the aim to explore the natural sequence variability and its role in the gene expression regulation. In order to identify functional allele variants, the 5’UTR intron was isolated and partially sequenced in 97 olive cultivars. The sequence analysis allowed to find a 117 bp insertion including two long duplications never found before in FAD2-2 genes in olive and the existence of many Intron-Mediated Enhancement (IME) elements. The sequence polymorphism analysis led to detect 39 SNPs. The candidate gene association study conducted for oleic and linoleic acids content revealed 7 SNPs and 1 indel significantly associated able to explain a phenotypic variation ranging from 7% to 16% among the years. Our study highlighted new structural variants within the FAD2-2 gene in olive, putatively involved in the regulation mechanisms of gene expression associated with the variation of the content of oleic and linoleic acid.